Reunion in France [videorecording (DVD)] - Borowsky, Marvin, 1907-1969; Connelly, Marc, 1890-1980; Crawford, Joan, 1908-1977; Wayne, John, 1907-1979 (John Wayne collection (Warner Bros.), 1942)
A Frenchwoman in Nazi-occupied Paris hides a downed American flyer and attempts to get him safely out of the country.